Brothers in the kitchen: the uprising, exodus and survival of a Tamily minority - Cyrus Sundar Singh (10838448) (2021)
Brothers In the Kitchen (BiTk), is a site-specific live-documentary performed with an audience inside a fully operational restaurant. The triumvirate of story, performance, and audience is used to create an interactive and immersive documentary experience incorporating oral storytelling, poetry, dance, music, archival materials and television— all performed live. BiTk is the story of the uprising, exodus and survival of Tamil Sri Lankan citizens who fled a brutal civil war and sought refuge in Canada. The ethnic conflict, between the Buddhist Sinhala majority and the Hindu Tamil minority, sparked a mass exodus following the deadly riots of Black July in 1983. Subsequently, a staggering 300,000 Tamils found asylum in Canada. Soon an inordinate number of them began work as cooks and dishwashers in many Canadian restaurants. This live documentary is performed thirty years after the arrival of the first boatload of Tamil refugees, found adrift off the coast of Newfoundland, in 1986.